Hybrid modernities : architecture and representation at the 1931 Colonial Exposition, Paris - Morton, P. A. (MIT Press, 2000)
The 1931 International Colonial Exposition in Paris was a demonstration of French colonial policy, colonial architecture and urban planning, and the scientific and philosophical theories that justified colonialism. The Exposition displayed the people, material culture, raw materials, manufactured goods, and arts of the global colonial empires. Yet the event gave a contradictory message of the colonies as the'Orient'-- the site of rampant sensuality, decadence, and irrationality -- and as the laboratory of Western rationality. In Hybrid Modernities, Patricia Morton shows how the Exposition failed to keep colonialism's two spheres separate, instead creating hybrids of French and native culture. At the Exposition, French pavilions demonstrated Europe's sophistication in art deco style, while the colonial pavilions were'authentic'native environments for displaying indigenous peoples and artifacts from the colonies. The authenticity of these pavilions'exteriors was contradicted by vaguely exotic interiors filled with didactic exhibition stands and dioramas. Intended to maintain a segregation of colonized and colonizer, the colonial pavilions instead were mixtures of European and native architecture. Anticolonial resistance erupted around the Exposition in the form of protests, anticolonial tracts, and a countercolonial exposition produced by the Surrealists. Thus the Exposition occupied a'middle region'of experience where the norms, rules, and systems of French colonialism both emerged and broke down, unsustainable because of their internal contradictions. As Morton shows, the effort to segregate France and her colonies failed, both at the Colonial Exposition and in greater France, because it was constantly undermined by the hybrids that modern colonialism itself produced